Scouting-based approach to strengthen social care character in elementary students' extracurricular activities - Putra, Ilzam Alfadila; Wakhudin, Wakhudin (Universitas Jambi, Indonesia, 2026)
This study investigated the strategic role of scouting extracurricular activities in strengthening the social care character of elementary students at SD Negeri Karanglo, Banyumas. Addressing challenges in character education, this research employed a descriptive qualitative approach, collecting data through observation, interviews, and documentation. The findings revealed that structured scouting activities such as camping, community service, and collective tasks function as a